2017
DOI: 10.18203/2320-1770.ijrcog20170401
|View full text |Cite
|
Sign up to set email alerts
|

A study to correlate histopathological findings in patients with abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding (AUB) is a common gynecological problem associated with considerable morbidity and significantly affects the patients. The aim of the study was to analyze the histopathological patterns of endometrium in patients presenting with AUB and also to determine the incidence of AUB in various age groups.Methods: This is a retrospective study, conducted in the Department of Obstetrics and Gynaecology, in a tertiary care teaching hospital, Mumbai, India from March 2016 till date. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
4
10
0
Order By: Relevance
“…In this, most of the women were belongs to the age group of 41-50 years (50%) and only (7.33%) of women belong to the age group of 13-20. Earlier studies (Shukla et al, 2017) showed that 53% of women were in the 41-50 age group compared to others, and thus, the study correlates with our study.…”
Section: Resultssupporting
confidence: 92%
“…In this, most of the women were belongs to the age group of 41-50 years (50%) and only (7.33%) of women belong to the age group of 13-20. Earlier studies (Shukla et al, 2017) showed that 53% of women were in the 41-50 age group compared to others, and thus, the study correlates with our study.…”
Section: Resultssupporting
confidence: 92%
“…In present study most of AUB patients belonged to 41-50 year age group, multiparous and had HMB as main complaint same as Shukla et al 19 Bashir et al also found menorrhagia (56.73%) as most common presenting complaint. 20 Incidence of heavy menstrual bleeding in this age group is more common; this may be due to the fact that as women approaches menopause, decrease number of ovarian follicle and increase resistance to gonadotropic stimulation, result in anovulatory cycles.…”
Section: Discussionsupporting
confidence: 78%
“…We found that leiomyoma (AUB-L 30%) was the most common cause of AUB closely followed by adenomyosis (AUB-A, 29.66%) which was in accordance with studies by other authors. [78910] Age is suggested to be an important risk factor with a lifetime risk more than 60% in women with age over 45 years. [789]…”
Section: Discussionmentioning
confidence: 99%
“…[78910] Age is suggested to be an important risk factor with a lifetime risk more than 60% in women with age over 45 years. [789]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation